Sediment dynamics of an artificially deepened mesotidal coastal lagoon: An environmental magnetic investigation of Tauranga Harbour, New Zealand. (15th July 2017) - Badesab, Firoz; von Dobeneck, Tilo; Briggs, Roger M.; Bryan, Karin R.; Just, Janna; Müller, Hendrik
Abstract: Tauranga Harbour, New Zealand's largest barrier-enclosed coastal lagoon, comprises two sub-basins with separate catchments, inlets and tidal channel systems. This study sets out to assess and investigate the sediment dispersal system of Tauranga Harbour using standard environmental magnetic and sedimentological methods. Compilations of rock magnetic and grain size data of surficial sediments collected from inflowing rivers, various estuarine environments (estuaries, tidal flats and tidal channels) and the adjacent nearshore mirror the net and differential sediment fluxes into and through the two sub-basins of this lagoon. For all studied depositional environments, the magnetogranulometric ratios SIRM/κ and ARM/κ are positively correlated with magnetic mineral content (SIRM, ARM, χ) in the sense that larger magnetic particles are associated with higher magnetic enrichment. Grain-size analyses show that magnetic enrichment during particle transport and deposition can result from grain-size as well as from grain-density fractionation. The periodically changing accumulation/erosion conditions provide for a selective retention of specific grain sizes and an enhancement of the heavier magnetic mineral particles. Magnetic crystal size and clastic grain size correlate poorly over the whole study area, but group within similar depositional environments. Coarser magnetic and clastic grain sizes and higher magnetite enrichment in the southern sub-basin can be reconciled with episodic flood runoff of the Wairoa River and a much larger, artificially deepened southern tidal inlet which likely enables higher tidal current velocities. Our approach of combining magnetic and clastic grain-size could be successfully implemented to establish a conceptual model of sediment dynamics and gravitational sorting within Tauranga Harbour.